The role of sodium croscarmellose in controlled drug release from oral solid dosage forms - Martins, Lucas Rafael Chambel (2022)
Trabalho Final de Mestrado Integrado, Ciências Farmacêuticas, 2021, Universidade de Lisboa, Faculdade de Farmácia.